Building Organizational Competitiveness By Building Convergence Of Business Strategy And Hr Strategy - Zukra Budi Utama; Thamrin Abdullah; Suparno Eko Widodo (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
How organizations survive following global phenomena in the form of increasingly random and unpredictable changes, which have now entered the industrial era 4.0. by increasing the acceleration of internet-based multi-media computer technology, in communication and control systems that are integrated with automation systems? Organizations must make a big leap by realizing the convergence of business strategies with HR strategies. Business and HR strategies are not only unidirectional but united in harmony. Where HR can respond to changes in the external and internal environment that affect business strategies, right at the moment the changes occur, so that convergence is always realized and sustained sustainably, then the focus of innovation drives the achievement of target organizations. Two things must be done to unite is to align the direction of departmental policies - as standard guidelines for individual work processes - with the direction of organizational strategy, then develop HR to be able to build integrated systematic work processes to eliminate routine work, so that the full focus of innovation responds to each convergence of disruptive changes. Our research in measuring the distance of policies from work functions to business strategies in private organizations, found an average achievement of 50%, to make improvements that reach 100%. For research conducted in public organizations, it was found that the achievement was very small, namely below 20%. The smaller the level of achievement the further away the organization is from the position of convergence. For this reason, HRD must build a Strategic KPI that encourages all management functions in line with organizational strategy, while developing Strategic HR to be ready to follow global developments.